Anti-inflammatory effects of ý-3 polyunsaturated fatty acids on fetal membranes. (16th November 2010) - Frew, L; Leask, R; Riley, SC; Stock, S
Abstract : Background: The fetal membranes contribute to the rise in pro-inflammatory cytokines during parturition that play a role in the onset of labour. In pregnancy, dietary supplementation with ω-3 polyunsaturated fatty acids (PUFAs) can prolong gestation and decrease preterm birth.1 However, mechanisms of these effects are unclear. There has been recent interest in anti-inflammatory actions of ω-3 PUFAs in other tissues, but their effect on the fetal membranes is largely unstudied. Objective: To determine whether eicosapentaenoic acid (EPA) and docosahexanoic acid (DHA) have an anti-inflammatory effect on the fetal membranes. Method: Amnion and chorion explants were obtained at elective caesarean section (n=6) and cultured with EPA 50 μM, DHA 50 μM or a combination of EPA and DHA for 24 h. Production of the inflammatory cytokines IL-6, IL-8, IL-1 and MCP-1 was determined by enzyme-linked immunosorbent assay of culture media. Data was analyzed by analysis of variance. Results are expressed as median and interquartile range. Results: In the amnion, treatment with a combination of EPA and DHA significantly reduced production of IL-6 (11.75 (9.3–156.9) vs 265.2 (64.4–865.7) p<0.05), IL-8 (359.8 (241–2316) vs 7623 (4748–8761) p<0.05) and MCP-1 (213.4 (15.6–433.6) vs 1160 (186.9–2783) p<0.05) compared to control. Production of IL-1 was undetectable in both control and treated samples. In the chorion EPA and/or DHA treatment had no effect on IL-6, IL-8 or IL-1 production, but did significantly reduce production of MCP-1 (448 (231.2–1311) vs 3601 (1724–5874) p<0.05). Conclusion: ω-3 PUFAs have an anti-inflammatory effect on fetal membranes. This may contribute to their ability to prolong gestation.